Implementasi Pengamanan Sistem Informasi Personel Berbasis Website - Resti Indah Paramita Sari; Anggraini Puspita Sari; Gatut Yulisusianto (Universitas Merdeka Malang, 2021)
The SIP (Personnel Information System) is designed to assist staff in managing the personal data of STTAD on the website. This SIP is for personnel who need personal data quickly. In the STTAD environment, the current HR information system is still operated manually. Personnel who need personal data should contact the Administrative Personnel (TS) to obtain the data required by the personnel. Through XAMPP, PHP, MySQL and PHPMyAdmin will later be used as an environment for developing SIP websites that can be accessed on the Internet. SIP can display Curriculum Vitae (RH) data and dossiers according to employees who successfully logged in at that time. SIP can be accessed by users (users) online. As well as personal data that was entered by the administrator into the database and then registered in the domain house (domain name) so that he receives the domain address and the user can open it through a web browser. Which later this system can be visited by the user through a web browser and make it easier for staff in terms of searching for personal data of staff.